European intersocietal recommendations for the biomarker-based diagnosis of neurocognitive disorders - Frisoni, Giovanni; Festari, Cristina; Massa, Federico; Cotta Ramusino, Matteo; Orini, Stefania; Aarsland, Dag; Agosta, Federica; Babiloni, Claudio; Borroni, Barbara; Cappa, Stefano F.; Frederiksen, Kristian S; Frölich, Lutz; et al. (The lancet, 2024)
The recent commercialisation of the first disease-modifying drugs for Alzheimer's disease emphasises the need for consensus recommendations on the rational use of biomarkers to diagnose people with suspected neurocognitive disorders in memory clinics. Most available recommendations and guidelines are either disease-centred or biomarker-centred. A European multidisciplinary taskforce consisting of 22 experts from 11 European scientific societies set out to define the first patient-centred diagnostic workflow that aims to prioritise testing for available biomarkers in individuals attending memory clinics. After an extensive literature review, we used a Delphi consensus procedure to identify 11 clinical syndromes, based on clinical history and examination, neuropsychology, blood tests, structural imaging, and, in some cases, EEG. We recommend first-line and, if needed, second-line testing for biomarkers according to the patient's clinical profile and the results of previous biomarker findings. This diagnostic workflow will promote consistency in the diagnosis of neurocognitive disorders across European countries.
Online verfügbar: 14. Februar 2024